Ferrocene Analogs of Brooker S Merocyanine: A New Library of Organometallic Inverted Solvatochromic Dyes - Aliaga-Vidal, C; Aliaga-Vidal, C; Dominguez-Caru, M; Martinez-Gomez, F; Aburto-Bernal, I (Royal Society of Chemistry, 2023)
Four organometallic dyes with ferrocene as the electron donor group and pyridinium or quinolinium acceptor groups were synthesized and their spectral behavior was recorded in various solvents with different polarities. Based on the degree of annulation of the acceptor moiety or the orientation of the donor/acceptor pair, the four dyes studied showed inverted solvatochromism at different solvent polarities. A multiparametric study of the dyes’ solvatochromic band showed that solvent acidity, dipolarity, and polarizability were mainly responsible for their inverted behavior, which originated from an internal charge transfer from the ferrocene fragment to the acceptor group. 1H NMR at various temperatures and EPR spectra showed no isomeric contamination or iron oxidation in their inverted solvatochromism. Finally, the present series illustrates a method to synthesize novel ferrocene-based inverted dyes by replacing the phenolate, a well-known organic electron donor group traditionally used in solvatochromic inverted dyes, with a ferrocene moiety, which proved to be an effective electron donor group. © 2023 The Royal Society of Chemistry.